IMPROVING THE OWNER-CONTRACTOR RELATIONSHIP THROUGH TRUST-BASED PREQUALIFICATION IN GREEN BUILDING PROJECTS - Gurgun, Asli Pelin; Koc, Kerim; Durdyev, Serdar (COLLEGE PUBLISHING, 2022)
A competent contractor can be regarded as a catalyst to deliver a truly sustainable building and thus help to mitigate detrimental impacts to the built environment. The prequalification phase provides confidence to the owner to achieve a project's sustainability requirements and reinforcing a mutual relationship with the selected contractor. This study proposes a decision framework for green building (GB) prequalification, which aims to improve the owner/contractor relationship. A comprehensive literature review was conducted to identify prequalification factors. To draw attention to GB projects and trust-based prequalification factors, a focus group discussion was performed with GB experts. A decision framework consisting of 12 relationship-based factors was then subjected to a fuzzy decision-making trial and evaluation laboratory (F-DEMATEL) method. The followed methodology aided the determination of the relationship-based prequalification factors, specification of the importance of factor degrees, illustration of the interrelationship among factors and consequently reveal the most causal factors that might contribute significantly to the improvement of the owner and contractor (O&C) relationship in GB projects. Results pointed out the importance of financial factors, while the same factors were found to be the driving force behind the improved relationship between O&C. Pertinent literature on prequalification in GB projects are limited, and no prior indepth study has investigated the prequalification phase based on trust and the mutual relationship between O&C. Highlighting the gap in the literature about trust-based contractor selection models, the proposed study can be useful to minimize conflicts and claims between the O&C, which could positively influence direct owners to consider GB projects.
Keywords: contractor prequalification; green building; relationship; fuzzy DEMATEL; DECISION-MAKING MODEL; DEMATEL METHOD; CONSTRUCTION; BARRIERS; SELECTION; CRITERIA; IMPLEMENTATION; IDENTIFICATION; SUCCESS; Architecture